2016
DOI: 10.1002/prep.201600062
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Interphase Stiffness and Percolation on the Behavior of Solid Propellants

Abstract: Atomic force microscopy has provided access to local moduli for propellants prepared with bonding agents, which create a stiffness gradient in the matrix producing a stiffer interphase surrounding the fillers. The reinforcing impact of the bonding agent appears up to some distance and interphase percolation is observed. In order to better understand the impact of bonding agents on the stress and strain at break of propellants, finite element simulations are performed. Two‐dimensional periodic cells containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Micro scale experiment is to characterize the microstructure and composition of the propellant at the atomic and molecular levels, and quantitatively express the bonding performance and damage degree of the interface by the molecular arrangement, chemical bond type and number of the bonding interface in a certain state. At present, there are some literatures about the interfacial stiffness using atomic force microscopy [101]. However, there is no report on the interface observation experiment at the molecular level.…”
Section: Microscale Experimentsmentioning
confidence: 99%
“…Micro scale experiment is to characterize the microstructure and composition of the propellant at the atomic and molecular levels, and quantitatively express the bonding performance and damage degree of the interface by the molecular arrangement, chemical bond type and number of the bonding interface in a certain state. At present, there are some literatures about the interfacial stiffness using atomic force microscopy [101]. However, there is no report on the interface observation experiment at the molecular level.…”
Section: Microscale Experimentsmentioning
confidence: 99%
“…It scans the surface of a material with a very small probe (<10 nm) and records the three-dimensional morphology of the material surface based on the change in the interaction force. Toulemonde et al [92] observed the modulus in micro-scale by AFM and obtained the clearly edges of white filler particles, dark gray matrix, and light gray interphase. The Young's modulus evolution curve showed that the interphase modulus was about five times of that of the matrix (5 MPa).…”
Section: Micromorphological Analysismentioning
confidence: 99%
“…The high volume fraction of particles [31], the nonlinear hyperelastic behavior of the elastomer matrix, the particle size [5,10,14,31] and the matrix/particles adhesion [11,14,15] give very specific tensile properties to solid propellants compared to other class of filled polymer matrix. For instance, it has been showed that damage by filler/matrix debonding has a very significant effect on the mechanical behavior of solid propellants [20,3,1,26] that is not fully understood despite recent studies [28,29].…”
Section: Introductionmentioning
confidence: 99%